Immediate Implant Placement and Immediate Loading in the Aesthetic Zone: A flapless Approach - Pokharel, Savvy; Dhami, Bhageshwar; Paudel, Shristi (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Replacing missing or failing teeth with implants can be a clinical challenge, especially in the aesthetic area, because patients expect an esthetically ideal prosthesis besides the osseointegration of implants. In this regard, immediate placement of implants with immediate loading is preferred by the patients, for the fewer surgeries involved and the immediate restoration of the potential edentulous sites. This article aims to present a case report of immediate placement of implant and immediate loading of the maxillary right lateral incisor.